The Impact of Transformational Leadership Style and Motivation from Within on The Quality of Public Services Through Organizational Commitment in The Social Services Department of West Tanjung Jabung District - Idris, Idris; Zahari, M.; Akbar, Ali (Dinasti International Journal of Digital Business Management, 2025)
Public service quality, organizational commitment, intrinsic motivation, and transformational leadership style are all intended to be described in this study.  Additionally, it seeks to ascertain and examine how Motivation from within and transformational leadership style impact the caliber of public service via organizational commitment. This study was carried out in Indonesia's Jambi Province at the West Tanjung Jabung Regency's Social Services Office.  In this investigation, both primary and secondary data were employed.  There were 100 responders in the sample.  Sampling was done using proportional stratified random sampling.  Descriptive and quantitative analysis were the methods employed for analysis.  A partial least squares (PLS) method combined with path analysis was employed in the quantitative study.  Software called SmartPLS 3.0 used to help process the data. According to the descriptive study, the transformational leadership style has been applied rather successfully.  Staff members have been highly motivated by intrinsic motivation.  At the same time, organizational dedication is rated as strong.  Public service quality is likewise classified as good. According to the verification analysis's findings, organizational commitment and the caliber of public services are positively and significantly impacted by transformational leadership and intrinsic motivation.  Increased organizational commitment has an impact on the quality of public services, and improvements in transformational leadership styles and Motivation from within help to support this. Additionally, it has been demonstrated that a key mediating element between the impact of leadership style and intrinsic drive on the quality of public service is organizational commitment.  These findings highlight how crucial transformative leadership and employee Motivation from within are to fostering dedication and enhancing public services